Collective Bargaining and Wage Equalization in Canada’s Iron & Steel Industry, 1939-1964 - Williams, Bryan (Relations industrielles / Industrial Relations, 1971)
This paper is one in a series being prepared by the Labour-Management Section of the Federal Department of Labour's Economies and Research Branch. It has three purposes. First, to highlight significant developments and characteristics in collective bargaining in the industry. Second, to determine the extent to which wage equalization is present in the industry. Third, to identify the influences that have contributed to these equalizing tendencies.